(untitled) (Global Journal of Science Frontier Research, 2018)
Mudbanks are the unique coastal phenomena with distinct patches of turbid and calm water with a high load of suspended sediment appearing close to the shore during rough sea. The occurrence and migration of mudbanks influence the coastal dynamics and coastline stability significantly. A typical mudbank formation was recently identified along the southern end of the east coast of India near Vedaranyam after the occurrence of Tsunami in 2004. A detailed study was carried out on the coastal morphology, geology, waves, currents, tides and other oceanographic parameters in the sea between Vedaranyam and Velankanni covering 35 km stretch during 2015 to 2016. The extent of clay deposition on the seabed and the formation of mudbank is more on the south side near Vedaranyam and reduce towards north near Velankanni.